Pre-treatment with ulipristal acetate before ICSI procedure: a case report - Wdowiak, Artur (Menopause Review/Przegląd Menopauzalny, 2013)
Epidemiologic data indicate that infertility is a common global problem being diagnosed in approximately one sixth of all couples. One of the reasons responsible for the inability to conceive is the presence of uterine fibroids. Many reports published recently have emphasized the high efficiency of ulipristal acetate in the treatment of uterine fibroids. In June 2012, a 35-year-old woman reported to the Non-Public Health Care Unit “Ovum Reproduction and Andrology” in Lublin for continued treatment of infertility. However, ultrasound performed on the day of the visit at Ovum showed two intramural uterine fibroids: one of them, size 2.26 cm × 2.53 cm, was located in the front uterine wall touching the endometrium and the other one with a diameter of 1.2 cm was located in the posterior uterine wall, not compressing the endometrium. Taking all of this into consideration along with the treatment conducted so far, the couple has been qualified for an ICSI (intracytoplasmic sperm injection) procedure. Due to the presence of the fibroid in the front wall of the uterus, which might have adversely affected embryo implantation in the previous IVF procedures, an attempt was made to reduce the fibroid volume with 3-month treatment with Esmya 5 mg 1 × 1 given for 84 days. Ultrasound performed after discontinuation of Esmya treatment showed normal size of the uterus with smooth contours and the previously detected intramural fibroid located in the posterior wall, was found to have a diameter of 1.08 cm, illustrating a reduction from pre-treatment size. The fibroid located in the front wall of the uterus previously detected by ultrasound was no longer visible. The patient underwent ICSI treatment. The risk of multiple pregnancies was reduced by an appropriate selection of a single blastocyst for transfer. Pregnancy was achieved and further ultrasound confirmed normal anatomical structure of the fetus and the absence of other fibroids.